Recommendations for the dental management of adult patients with head and neck cancer in Slovenia treated with radiation therapy - Aleš Fidler; Aleksander Aničin; Vojko Didanović; Tadej Dovšak; Boris Gašpirc; Aleš Grošelj; Andrej Kansky; Matic Koren; Jana Krapež; Hojka Kuralt; Marko Kuralt; Boštjan Lanišnik; et al. (Onkologija, 2022)
Recommendations for the dental treatment of patients with head and neck cancer (HNC) in Slovenia treated with radiation follow the recommendations and guidelines of the Royal College of Surgeons of England created in association with the British Society for Disability and Oral Health, the Recommendations for the treatment of patients with head and neck cancer in Slovenia and at the same time consider the existing capabilities of the Slovenian health care system. The recommendations aim to prevent or reduce complications in the oral cavity due to radiation therapy. They define the dental care before, during and after radiation therapy at all three levels of dental care, which ensures the timeliness and accessibility of dental care. The recommendations represent a unified opinion of all stakeholders in the field of dental treatment of HNC patients in the country.